POLICE ROLE IN IDENTIFYING FINGERPRINT BUSINESS CRIME (Studies in the Central Java Police) - Indah Setyowati; Ika Setya Arini (Jurnal Pembaharuan Hukum, 2018)
Fingerprint identification is a technical assistance Police and plays an important role in proving the identity of the perpetrators of criminal acts, able to support a rapid, precise and accurate and to improve the effectiveness and efficiency in law enforcement. This study aims to determine the role of the police in the process of identifying fingerprint to uncover the perpetrators of criminal acts and to identify constraints as a barrier to the implementation of the process of identifying fingerprints by the police to uncover the perpetrators of criminal acts. This study uses empirical juridical approach to analyze the problem by combining the juridical aspect is legislation that was secondary data and empirical aspects by conducting interviews and observations at the site of research is the primary data. Results showed that: 1. The Role of the Police in identifying the perpetrator Crime Fingerprint carried out in several stages conducted by the Criminal dactyloscopy field dactyloscopy Unit (Daktikrim) under Section Identification Ditreskrimum Central Java Regional Police, in charge of the formulation, examination, comparison of equation fingerprint to reveal the identity of the offender. 2. Obstacles that Being inhibitors in Implementing Fingerprint Identification Process by the Police for Revealing Actors Crime: a. Constraints of the Police (Internal constraints) b. Constraints from outside the Police (External constraints).